2013
DOI: 10.1124/jpet.113.205435
|View full text |Cite
|
Sign up to set email alerts
|

Protective Properties of 2-Acetylcyclopentanone in a Mouse Model of Acetaminophen Hepatotoxicity

Abstract: Our previous research showed that enolates formed from 1,3-dicarbonyl compounds, such as 2-acetylcyclopentanone (2-ACP), could provide protection in cell culture models from electrophile-or oxidative stress-induced toxicity. In the present study, we evaluated the protective abilities of 2-ACP in a mouse model of acetaminophen (APAP) hepatotoxicity. Results show that oral APAP overdose (500 mg/kg) was nearly 90% lethal within 72 hours and that the resulting hepatotoxicity was associated with substantial changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 49 publications
3
50
0
Order By: Relevance
“…APAP and all experimental compounds were administered in phosphatebuffered polyethylene glycol. Previous studies demonstrated that this vehicle did not affect the experimental outcome (Zhang et al, 2013). As a general protocol, groups of mice (n 5 10-15) were pretreated by intraperitoneal injection (10 ml/kg; THA, 0.2-0.8 mmol/kg; PG, 0.4-2.4 mmol/kg) or oral administration (6 ml/kg; THA, 0.8-2.4 mmol/kg; PG, 0.8 and 2.4 mmol/kg) of putative hepatoprotectant followed 20 minutes later by oral (4 ml/kg) APAP (500 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…APAP and all experimental compounds were administered in phosphatebuffered polyethylene glycol. Previous studies demonstrated that this vehicle did not affect the experimental outcome (Zhang et al, 2013). As a general protocol, groups of mice (n 5 10-15) were pretreated by intraperitoneal injection (10 ml/kg; THA, 0.2-0.8 mmol/kg; PG, 0.4-2.4 mmol/kg) or oral administration (6 ml/kg; THA, 0.8-2.4 mmol/kg; PG, 0.8 and 2.4 mmol/kg) of putative hepatoprotectant followed 20 minutes later by oral (4 ml/kg) APAP (500 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…A separate group of animals were given vehicle by intraperitoneal injection or oral administration followed 20 minutes later by oral APAP. To define the temporal limitations of hepatoprotection, groups of mice were treated with oral APAP (500 mg/kg) followed Enolate-Forming Compounds Prevent Acetaminophen Toxicity 60 minutes later by intraperitoneal or oral administration of putative protectant (Zhang et al, 2013). Control mice received an intraperitoneal/ oral sequence of vehicle injections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations